Development of 6kw Variable Power Supply Leading to Knowledge Extraction for Power Electronic Design Aid System Database - Adam, Yousif Abbaker (1999)
Expert systems are starting to play an important role in this era of knowledge. As we are moving from information age to knowledge age; management and organisation of human expertise will have a great impact in all aspect of life in terms of time saving and money. This project is targeted to feed the expert system with the knowledge that is extracted during the process of design and development of a power supply. The design of the power supply is the major part of the work while the extraction of knowledge comes after. The power supply circuit is composed of three major stages; the input power AC to DC conversion circuit, the Buck converter power circuit that is controlled by PWM signal, and the control circuit which includes the logic, isolation and driving circuits. Switching technique is employed based on duty cycle control by which the different outputs is obtained. Insulated Gate Bipolar Transistor (lGBT) is used as a power switch protected by snubber circuit. A negative feedback is employed to maintain constant output. The power supply design is simulated using PSpice and the hardware circuit is then built and tested. The complete design of the power supply is achieved and as the expected results are obtained leading to the knowledge extraction process during the power supply development, by which this work contributes to the Power Electronic Design Aid System database (PEDAS).